EVALUASI PROGRAM DISTRIBUSI SUBSIDI LPG 3 KG DI KOTA SURABAYA - Febrian, A. Tsani Sabhan; Pratama, Virdean Paulia; Oktaviani, Nabila; Margaretha, Karyn; Rotua Simanjuntak, Maria Equina (PRAJA: Jurnal Ilmiah Pemerintahan, 2024)
The update of policies related to mandatory ID cards and family cards for the target group has resulted in the 3 kg LPG subsidy distribution program in the city of Surabaya needs to be evaluated to find out the direction of the program. The evaluation of the 3 kg LPG subsidy distribution program in the city of Surabaya aims to find out the results of the implementation of the 3 kg subsidized LPG distribution policy in the city of Surabaya. The research method uses qualitative method with a descriptive approach to provide a complete picture according to the topic discussed. This study uses policy evaluation theory by William N. Dunn. Data collected by interviews, observations and documentation. Then, data analysis techniques by Miles & Huberman were also used in data collection, data reduction, data presentation, and conclusion drawn. The results of the study with evaluation indicators such as effectiveness, adequacy, equity, responsiveness, and accuracy have shown that the implementation of the 3 kg LPG subsidy program in the city of Surabaya has been well realized. Through the use of Merchant Apps Base Pertamina Lite, it also contributes to the process of distributing 3 kg LPG subsidies evenly for community groups who are entitled to receive it. The Surabaya City Government through the Subdivision of Planning and Supervision of Micro, Small Economy and Natural Resources of the Economy and Natural Resources Section always conducts thorough supervision to find out the development of the program so that it is more on target.